2020
DOI: 10.1111/trf.16180
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic bactericidal effects of pairs of photosensitizer molecules activated by ultraviolet A light against bacteria in plasma

Abstract: Background The current approach to reducing bacterial contamination in blood transfusion products is through detection or pathogen reduction methods, some of which utilize ultraviolet (UV) light photosensitizers. A small number of photosensitizers are being used as single agents in combination with UV light, but their efficacy can be limited against some pathogens. Benzophenone (BP) and vitamins B1, B6, and K3 have been identified as effective UVA photosensitizers for inactivation of bacteria. We evaluated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The UVA photosensitizer application appears to be an attractive approach for whole blood since it has already proved to be successful in platelet and plasma pathogen reduction. We have previously shown that the UVA/VK5 combination, as well as combinations of other vitamins with UVA light, can produce a reduction of bacteria in suspension 6,8 5,7 Our current results show that VK5 and UVA photodynamic treatment can also reduce viral titers in human plasma thus expanding the pathogen reduction potential of this combination.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The UVA photosensitizer application appears to be an attractive approach for whole blood since it has already proved to be successful in platelet and plasma pathogen reduction. We have previously shown that the UVA/VK5 combination, as well as combinations of other vitamins with UVA light, can produce a reduction of bacteria in suspension 6,8 5,7 Our current results show that VK5 and UVA photodynamic treatment can also reduce viral titers in human plasma thus expanding the pathogen reduction potential of this combination.…”
Section: Discussionmentioning
confidence: 51%
“…Riboflavin binds to nucleic acids (DNA or RNA) bases leading to pathogen inactivation mainly through the generation of free reactive radicals, which enhances the formation of oxidized nucleotides 3,4 . Other approaches with different photosensitizers, such as benzophenone and vitamins B1, B6, K3, and K5 combined individually with UVA irradiation have been shown to be effective for the inactivation of bacteria in plasma 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…Different abatement rate among bacterial strains may be explained by the different biological dispositions and expressions of endogenous photosensitizers in different species 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Light is considered the single most important contributor to bacterial die-off in aquaculture water [17,18]. A bactericidal effect of light was achieved that caused a rapid decrease in the colony-forming ability of bacteria [19,20]. Solar UV light is highly bactericidal, causing direct photobiological DNA damage in bacteria [21].…”
Section: Plos Onementioning
confidence: 99%